Improving the Ability to Manage Libraries for School Administration Staff and Teachers Through In-House Training (IHT) at Jumblangan Elementary School, Samigaluh, Kulon Progo Regency for the 2021/2022 Academic Year - Herlina Ana Susanti (International Journal of Chemistry Education Research, 2022)
This study aims to improve the quality of library management and services as well as the ability of the principal in managing activities through in-house training at SD Negeri Jumblangan, samigaluh, Kulon Progo regency, for the 2021/2022 academic year. This type of research is school action research which was carried out for 3 cycles. Where each cycle consists of the following 2 meetings if the research in cycle II has met the indicators of success, the research can be ended. The corrective steps are based on research procedures, which are carried out based on the stages of planning, implementation, observation, and reflection. The research subjects were librarians and teachers of SD Negeri Jumblangan, samigaluh, and Kulon Progo regency for the academic year 2021/2022, totaling 8 people. The results showed that the implementation of the first cycle at the first meeting reached 78.00% with the "enough" category. Furthermore, the results in the first cycle of the 2nd meeting obtained a percentage of 84.25%. When compared with cycle ii at the first meeting there was an increase of 6.25%. Furthermore, the results of the research in the second cycle at the first meeting obtained a percentage of 88.00%. So it can be said that there is an increase of 3.75% in the first cycle of the meeting at the second meeting